Guidelines for the nursing management of gestational diabetes mellitus: An integrative literature review - Gwendolyn Patience Mensah; Wilma ten Ham‐Baloyi; Dalena (R.M.); Sihaam Jardien‐Baboo (Wiley, 2020)
Abstract Aims and objectives An integrative literature review searched for, selected, appraised, extracted and synthesized data from existing available guidelines on the nursing management of gestational diabetes mellitus as no such analysis has been found. Background Early screening, diagnosis and management of gestational diabetes mellitus are important to prevent or reduce complications during and postpregnancy for both mother and child. A variety of guidelines exists, which assist nurses and midwives in the screening, diagnosis and management of gestational diabetes mellitus. Design An integrative literature review. Methods The review was conducted in June 2018 following an extensive search of available guidelines according to an adaptation of the stages reported by Whittemore and Knafl (2005, Journal of Advanced Nursing, 52, 546). Thus, a five‐step process was used, namely formulation of the review question, literature search, critical appraisal of guidelines identified, data extraction and data analysis. All relevant guidelines were subsequently appraised for rigour and quality by two independent reviewers using the AGREE II tool. Content analysis was used analysing the extracted data. Results Following extraction and analysis of data, two major themes were identified from eighteen (N = 18) guidelines. These were the need for early screening and diagnosis of gestational diabetes mellitus and for nursing management of gestational diabetes mellitus (during pregnancy, intra‐ and postpartum management). Various guidelines on the nursing management of gestational diabetes mellitus were found; however, guidelines were not always comprehensive, sometimes differed in their recommended practices and did not consider a variety of contextual barriers to the implementation of the recommendations. Conclusion Critically, scrutiny of the guidelines is required, both in terms of the best evidence used in their development and in terms of the feasibility of implementation for its context. Relevance to clinical practice This study provides a summary of best practices regarding the diagnosis, screening and nursing management of gestational diabetes mellitus that provide guidance for nurse-midwives on maternal and postpartum follow‐up care for women at risk or diagnosed with gestational diabetes mellitus.